Malnutrition and Its Correlation with Egg Production Quantity and the Human Development Index in South Sumatra, Indonesia: Malnutrition, Egg Supply, and Human Development - Bertliussaza; Rifansyah, Ogi (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2025)
Egg production is one of the determining factors for improving the nutrition of the community, which, in turn, contributes to an increase in the Human Development Index. Therefore, it is essential to examine the relationship between egg production quantity, malnutrition, and the Human Development Index. This research utilizes secondary data from the South Sumatra Central Statistics Agency regarding the quantity of egg production, the community development index, and malnutrition in South Sumatra from 2018 to 2022. The data will be processed using the Smart-Pls 4 application, employing the Structural Equation Modeling (SEM) technique. Based on the results of hypothesis testing, it is also known that the second hypothesis, stating that Nutrition has a positive influence on Production, is accepted because the original sample is positively 0.724 > 0, indicating a positive influence. Furthermore, the T Statistics value is 6.470 > 1.645, and the P Values is 0.000 < 0.05, signifying a significant impact. The results indicate a correlation were higher levels of malnutrition lead to increased egg production. The implications of these findings suggest that despite a high quantity of eggs produced, not many people are able to consume eggs. This could also raise concerns about food insecurity in South Sumatra.